Evaluation of thermal and dynamic impacts of summer dust aerosols on the Red Sea - Cahill,B; Toumi,R; Stenchikov,G; Osipov,S; Brindley,H (Journal of Geophysical Research: Oceans, 2017)
The seasonal response of upper ocean processes in the Red Sea to summer-time dust aerosol perturbations is investigated using an uncoupled regional ocean model. We find that the upper limit response is highly sensitive to dust-induced reductions in radiative fluxes. Sea surface cooling of −1°C and −2°C is predicted in the northern and southern regions, respectively. This cooling is associated with a net radiation reduction of −40 W m−2 and −90 W m−2 over the northern and southern regions, respectively. Larger cooling occurs below the mixed layer at 75 m in autumn, −1.2°C (north) and −1.9°C (south). SSTs adjust more rapidly (ca. 30 days) than the subsurface temperatures (seasonal time scales), due to stronger stratification and increased mixed layer stability inhibiting the extent of vertical mixing. The basin average annual heat flux reverses sign and becomes positive, +4.2 W m−2 (as compared to observed estimates −17.3 W m−2) indicating a small gain of heat from the atmosphere. When we consider missing feedbacks from atmospheric processes in our uncoupled experiment, we postulate that the magnitude of cooling and the time scales for adjustment will be much less, and that the annual heat flux will not reverse sign but nevertheless be reduced as a result of dust perturbations. While our study highlights the importance of considering coupled ocean-atmosphere processes on the net surface energy flux in dust perturbation studies, the results of our uncoupled dust experiment still provide an upper limit estimate of the response of the upper ocean to dust-induced radiative forcing perturbations.